2012
DOI: 10.1111/tpj.12017
|View full text |Cite
|
Sign up to set email alerts
|

Integrative analysis of chromatin states in Arabidopsis identified potential regulatory mechanisms for natural antisense transcript production

Abstract: SUMMARYGenome-wide analyses of epigenomic and transcriptomic profiles provide extensive resources for discovering epigenetic regulatory mechanisms. However, the construction of functionally relevant hypotheses from correlative patterns and the rigorous testing of these hypotheses may be challenging. We combined bioinformatics-driven hypothesis building with mutant analyses to identify potential epigenetic mechanisms using the model plant Arabidopsis thaliana. Genome-wide maps of nine histone modifications prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
164
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(181 citation statements)
references
References 42 publications
15
164
2
Order By: Relevance
“…We also examined specific histone modifications associated with the three types of RdDM loci using publicly available data [41]. We found that the ID and PD loci npg www.cell-research.com | Cell Research have significantly higher levels of two heterochromatin marks, H3K9me2 and H3K27me1 than the FD loci (Figure 5C and Supplementary information, Table S3).…”
Section: Dicer-independent Dna Methylation At Rddm Target Locimentioning
confidence: 99%
“…We also examined specific histone modifications associated with the three types of RdDM loci using publicly available data [41]. We found that the ID and PD loci npg www.cell-research.com | Cell Research have significantly higher levels of two heterochromatin marks, H3K9me2 and H3K27me1 than the FD loci (Figure 5C and Supplementary information, Table S3).…”
Section: Dicer-independent Dna Methylation At Rddm Target Locimentioning
confidence: 99%
“…H4K16ac is positively correlated with active marks (H3K9ac, H3K18ac, H3K4me2/3 and H3K36me2/3 15,[42][43][44] ) and anti-correlated with repressive modifications (H3K27me1 and H3K9me2 15,45 ) and histone variants H3.1 and H2A.W, which are required for heterochromatin condensation ( Fig. 2A).…”
Section: Combined Enrichment Of H4k16ac and H3k23ac Is Correlated Witmentioning
confidence: 99%
“…The histone modification ChIPsequencing datasets were obtained from previously published papers. 43,46,47,70 Pairwise association analysis between histone modification marks was calculated by Pearson correlation method. The P values was calculated by a Student t-test.…”
Section: Real-time Pcrmentioning
confidence: 99%
“…The antagonistic relationship between H3K36me3 and H3K27me3 has been previously noted within genes, together with the hypothesis that natural antisense transcript (NAT) production is repressed by a combination of cytosine methylation and H3K36me3. 55 In combination with our data, this may suggest that either NATs have an increased tendency to generate mobile sRNAs, or that this is a more general result applying to some subset of mobile sRNA loci.…”
Section: Classes Of Interaction and Histone Modificationmentioning
confidence: 69%
“…We further investigated differentiation between sRNA-methylome interaction classes through comparisons with the histone modification data of Luo et al 55 Peaks for 9 histone modifications were identified using the MACS2 pipeline 56 ; where data from multiple samples was available this was merged using DiffBind. 57 Overlaps between the locus classes and regions of histone modification (Fig.…”
Section: Classes Of Interaction and Histone Modificationmentioning
confidence: 99%